(NgLUBINNAQ GEOLOGIQ aRKTI^ESKOGO BASSEJNA (B/s - (NkISELEW(B, (N`RIJ gEORGIEWI^s ((NmOSKWA (B:s (NnEDRA(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 218-220 (50 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 220-223s
Keywords: (NoKEANY (B- (NgEOLOGIQ STRUKTURNAQ (B- (NsEWERNYJ lEDOWITYJ OKEANs; (NsEWERNYJ lEDOWITYJ OKEAN (B- (NgEOLOGIQ STRUKTURNAQs